1997
DOI: 10.1002/(sici)1097-4660(199703)68:3<257::aid-jctb619>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Thioesters in Non-conventional Solvents

Abstract: The feasibility of enzymatic thioesterification between oleic acid and butanethiol in n‐hexane, with the immobilised lipase (Lipozyme) from Mucor miehei, has been demonstrated. The immobilised enzyme quantity (100 mg), temperature (40°C), pH range (6–9) and water content (10%) were studied and their optimum values were determined. A preliminary kinetic study indicated a low butanethiol affinity for the enzyme (Km = 1·85 mol dm−3). Even when butanethiol was used without solvent, no substrate inhibition was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…The percentage of yields increased with increase in amount of enzyme up to 194 mg. At this point, all substrates are bound to the enzyme and addition of any enzyme molecule may cause a decrease in the yield due to the substrate limitations [28]. However, high amount of enzyme may cause diffusion which relates to mass transfer limitation [29]. Figure 7 represents the effect of varying molar ratio (octyl alcohol/adipic acid) on the synthesis of dioctyl adipate at 50°C, 195 min, and 200.5-mg enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of yields increased with increase in amount of enzyme up to 194 mg. At this point, all substrates are bound to the enzyme and addition of any enzyme molecule may cause a decrease in the yield due to the substrate limitations [28]. However, high amount of enzyme may cause diffusion which relates to mass transfer limitation [29]. Figure 7 represents the effect of varying molar ratio (octyl alcohol/adipic acid) on the synthesis of dioctyl adipate at 50°C, 195 min, and 200.5-mg enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to alkyl esters, it has been demonstrated that two immobilised fungal lipases (Lipozyme TM and Novozyme TM ) can catalyse the synthesis of thioesters from a carboxylic acid and a thiol (thioesterification) and from an ester and a thiol (transthioesterification) in low-water systems (Cavaille-Lefebvre & Combes, 1997; Caussette, Marty, & Combes, 1997). These findings suggest that lipases may play a role in the biosynthesis of flavour thioesters in dairy systems, provided that the key precursors, thiols (e.g., methanethiol) and fatty acids, are available in sufficient amounts and that the water activity is favourable (see Section 4.2).…”
Section: Article In Pressmentioning
confidence: 99%
“…Thus, lipase-catalyzed reactions in SCCO 2 have been carried out for such reactions as hydrolysis of tripalmitin (5) and canola oil (6); alcoholysis of cod liver oil (7) and palm kernel oil (8); glycerolysis of soybean oil (9); synthesis of oleoyloleate from oleic acid (10)(11)(12); acylation of glucose with lauric acid (13); thioesterification between oleic acid and butanethiol (14); transesterifications of milk fat with canola oil (15); tristearin with palm oil (16); palm oil with stearic acid (SA) (17); triolein with ethyl behenate and behenic acid (18,19); triolein with SA (20) and propyl acetate with geraniol (21); and randomization of fat and oils (22).…”
mentioning
confidence: 99%